Evaluation of Electronic Traffic Law Enforcement (E-TLE) Program in Medan City - Ritonga, Azri Dirgantara; Humaizi, Humaizi; Achmad, Nurman (Formosa Journal of Multidisciplinary Research, 2025)
The E-TLE program, or Electronic Traffic Law Enforcement, is an electronic-based traffic law enforcement system designed to increase efficiency in monitoring and enforcing traffic regulations. ETLE works by using various technological devices, such as surveillance cameras installed at various strategic points, including at road intersections, along highways, or in locations prone to violations. This research aims to analyze how the Electronic Traffic Law Enforcement (E-TLE) program is implemented in realizing traffic order for motorists in the city of Medan and to analyze what factors hinder of the program. This research uses qualitative methods. The results of this research show that the E-TLE program is not yet fully capable of realizing traffic order for motorbike drivers because there are still factors and obstacles in its implementation, such as a lack of awareness among motorbike drivers due to not fully understanding the performance of the E-TLE program. The lack of deterrent effect received by motorists and the lack of socialization information provided by the police regarding this program has caused motorists to assume that this program is just a formality.